Do Investors Tend to Overreact when Investing in Clean Energy Stock Indices? - Dias, Rui; Galvão, Rosa; Cruz, Sandra; Gonçalves, Sidalina; Irfan, Mohammad; Teixeira, Nuno; Alexandre, Paulo; Palma, Cristina; Almeida, Liliana (International Journal of Energy Economics and Policy, 2025)
Due to climate change, investors are increasingly interested in clean energy stocks attracting many investors due to clean energy prospects. This paper analyses investor overreactions to long-term prices in various clean energy stock indices, such as Clean Energy Fuels (CLNE), Global Clean Energy (GCEI), as well as the Dow Jones Industrials (DJI) stock index, over the period from 24 February 2022 to 23 May 2024. The results show that the Global Clean Energy (GCEI) clean energy stock index rejects H0 at the 16-day lag at a significance level of 1%; similarly, the Clean Energy Fuels (CLNE) index rejects the null hypothesis at lags 8, 9, 10, 11 and 12 days, both indices show negative serial autocorrelation, which means that price movements are not entirely random and are influenced by prior price movements. This evidence could mean that investors overreact to the information that reaches the market. On the other hand, the ETF (PWYF) and the Dow Jones Industrial Stock Index (DJI) show that the random walk hypothesis has not been rejected. In other words, these markets show that they are in equilibrium and that the existence of exaggerated reactions on the part of investors is not significant. The answer to the research question was partially accepted, so the Russian invasion of Ukraine in 2022 led to the partial presence of overreactions in these stock indices. In conclusion, investors operating in these markets should exercise caution and consider their risk tolerance before investing. Investors should, therefore, continue to monitor market trends and adjust their investment strategies accordingly.